Use of Augmented Reality in Illustrated Children's Books and an Application Example - KARAATA, EZGİ (My University, 2023)
This study aims to examine the relationship between augmented reality technology and illustrated children's books and convey the importance of children's literature by being supported with an application example. Withthedevelopments indigital technology deeply transforming visual media and the internet becoming an indispensable part of our lives, along with the widespread use of portable devices such as smartphones and tablets, it has also had an impact on traditional children's books. The opening of impressive visual worlds for children through augmented reality applications also reflects all of these. The study collected and presented data related to the history of augmented reality technology and the historical process of pop-up books, considered the predecessor of books designed with augmented reality. A literature review was conducted in chronological order to present the development of illustrated children's books produced with augmented reality technology. As part of the study, an augmented reality application was developed for a children's book project inspired by Hezârfen Ahmet Çelebi's flight from the Galata Tower, featuring traces of miniature art. The creation process and technical infrastructure of this application were also provided. Based on the information collected during the research and the experience gained from the illustrated book project, the study highlights the importance of using augmented reality technology in children's literature and provides suggestions to address the shortcomings in this field. Keywords: Illustration, Children’s Book, Augmented Reality, Pop-Up Books

Bu çalışmanın amacı artırılmış gerçeklik teknolojisi ile resimli çocuk kitapları arasındaki ilişkinin incelenmesi, bir uygulama örneği ile desteklenerek çocuk edebiyatındaki öneminin aktarılmasıdır. Dijital teknolojideki gelişmelerin görsel medyayı derinden değiştirmesiyle, internetin hayatımızın vazgeçilmez bir parçası haline gelmesi ve paralelinde akıllı cep telefonları, tablet gibi taşınabilir araçların geniş kitleler tarafından kullanılıyor olması, geleneksel çocuk kitaplarında da etkisini göstermiştir. Artırılmış gerçeklik uygulamalarının çocuklar için etkileyici bir görsel dünyanın kapılarını açması da bütün bunların bir yansımasıdır. Çalışmada artırılmış gerçeklik teknolojisinin geçmişine ve artırılmış gerçeklikle tasarlanmış kitapların atası sayılabilecek hareketli kitaplarla ilgili tarihsel sürece ait veriler toplanarak ortaya konmuştur. Artırılmış gerçeklik teknolojisi ile üretilmiş resimli çocuk kitaplarının gelişimini aktarmak amacıyla literatür taraması yapılmış ve kronolojik olarak sunulmuştur. Çalışmanın dâhilinde, Hezârfen Ahmet Çelebi’nin Galata Kulesi’nden uçuşuyla ilgili bir hikâye olan ve minyatür sanatından izler taşıyan çocuk kitabı projesi tasarlanarak, artırılmış gerçeklik uygulaması yapılmıştır. Yapılan bu uygulamanın yaratım süreci ve teknik altyapısı ile ilgili bilgilere yer verilmiştir. Araştırmanın sonucunda toplanan bilgiler ve resimli kitap projesi deneyimi ışığında, artırılmış gerçeklik teknolojisinin çocuk edebiyatında kullanımının önemi aktarılmış, bu alandaki eksikliklerden bahsedilerek bazı öneriler sunulmuştur. Anahtar Kelimeler: İllüstrasyon, Resimli Çocuk Kitapları, Artırılmış Gerçeklik, Pop-Up Kitaplar
Resimli Çocuk Kitaplarında Artırılmış Gerçeklik Kullanımı ve Bir Uygulama Örneği
Keywords: Illustration; Children’s Book; Augmented Reality; Pop-Up Books; İllüstrasyon; Resimli Çocuk Kitapları; Artırılmış Gerçeklik; Pop-Up Kitaplar